Summer blast : getting ready for fourth grade - Conklin, Wendy (Shell Education, 2016)
Blast away summer learning loss and prepare students for third grade with the engaging cross-curricular activities and parental support tools in this standards-based resource. Excite and energize students in the summer months with 9 weeks of fun, theme-based units focusing on key skills and objectives from third grade and the beginning of fourth grade. Full-color student practice pages bring 27 language arts, 27 mathematics, and 27 critical and creative thinking activities to life while supporting content learning in reading, writing, math, science, social studies, and art. With critical-thinking puzzles and a theme-based art activity for each unit, students will develop important 21st century skills. Including a Parent Handbook for Today's College and Career Readiness Standards, this resource also addresses key features and shifts of today's standards which prepares parents to help their child successfully navigate Common Core and other state standards. Additionally, parents are provided with easy-to-implement family activities that foster everyday learning including science labs, books to read aloud, and recommended educational websites and apps. --Publisher's description.